PENDIDIKAN ISLAM BERBASIS KEARIFAN LOKAL - Rustam Rustam; Ahmad Shofiyuddin Ichsan (Institut Agama Islam Negeri Palopo, 2020)
This research reveals Islamic education based on local wisdom at Islamic Boarding School ISC Aswaja Lintang Songo Piyungan, Bantul, Yogyakarta. This type of research is field research with a qualitative approach. The research data was taken from three sources, namely: 1). Observation several times, 2). Interviews with pesantren leaders, administrators, instructors, students, and residents around the pesantren, and 3). Documentation of various related information. The results show that all actions and activities carried out by pesantren residents (kiai, administrators, clerics, and students) at Islamic Boarding School ISC Aswaja Lintang Songo could be seen as a form of applying education and forming noble (uploading) personalities based on local wisdom. Therefore, this pesantren manages its education system in four ways, namely religious education, skills education, extracurricular education, and character education. Keywords: Islamic Education, Local Wisdom, Islamic Boarding School